Menumbuhkan Budaya Literasi Bahasa Inggris Melalui Extensive Reading di Taman Baca Masyarakat (TBM) Kota Tasikmalaya - Setyo Wati (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
This community service program is motivated by the low level of literacy skills of the Indonesian people. This fact proves that the literacy value of Indonesian people reading is still very low. According to TBM West Java data in 2017, the Tasikmalaya region in the districts and cities has more than ten scattered community reading parks, but most have not been maximally utilized by the surrounding community, especially for the availability of English books. Seeing the above phenomenon, it is necessary to have a solution in the community. This community service program offers a language literacy program using the Extensive Reading method as an effort to foster community literacy. The main reason for this literacy program is that literacy is the right of everyone and is the basis for learning throughout time. This program combines foreign language learning with community literacy programs. This activity involved TBM managers and children as participants in the activity. The Extensive Reading method is used in community service programs to foster community literacy. The results of these community service activities include a literacy program that introduces extensive reading methods in improving integrated and effective English language skills to help equalize education through integrated reading services in Nagarasari, Tasikmalaya city